Developments and Techniques in the Global Market: Exploring the Dynamics of Mergers and Acquisitions in the Global Market (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The increased competition in the global market has prompted the Companies to go global for mergers and acquisitions as an important strategic choice. Mergers & Acquisitions (M&A) are the strategic growth devices in the hands of more and more Companies not only to stay in the competition but also to extend their margins, market share and dominance globally. The scale and the pace at which merger activities are coming up are remarkable. In the sense, mergers and acquisitions has become a strategic concept to grow quickly for a number of leading companies’ world over. The booms in mergers and acquisitions suggest that the organizations are spending a significant amount of time and money either searching for companies to acquire or worrying about whether some other company will acquire them. Globalization, deregulation and technological improvements have resulted in increase in M&A across the globe. There is enormous literature existing in the advanced economies. However, very little information is available regarding M&A in India. Various sectors have witnessed differential involvement in M&A activity indicating higher participation by some. Particularly, certain sectors such as financial services and pharmaceuticals demonstrate higher M&A activity. To emphasise differential importance of sectors in M&A activity, it is necessary to conduct a sector-wise analysis. Accordingly, this study attempts to investigate the differential representation of various sectors in M&A. Further, it explores the role played by India in the rising global M&A activity. In light of this, it specifies the factors driving consolidation in the financial sector globally.